EVALUASI PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS DENGAN MODEL CIPP - Afifah Dyah Setyorini; Jamalludin Jamalludin (STAI Sangatta Kutai Timur, 2023)
This study aims to: (1) find out the context in limited face-to-face learning, (2) find out the input in limited face-to-face learning, (3) find out the process in limited face-to-face learning, (4) find out the results in limited face-to-face learning at SMP Negeri 2 North Sangatta. The method used in this study is the Context, Input, Process, Product (CIPP) model. The results of the study obtained data that (1) the context in face-to-face learning is limited by the unpreparedness of learning facilities and infrastructure, the low ability of teachers and students in the use of information technology, (2) input in face-to-face learning is carried out not by the objectives, strategies, and learning needs required by students. (3) The process of implementing limited face-to-face learning is carried out by conducting learning in an uncoordinated and non-contextual manner. (4) Online learning outcomes have decreased learning outcomes and face-to-face learning has increased scores above the KKM. The conclusion from this study is that the implementation of face-to-face learning is limited, and there is a decrease in academic value due to limited facilities and infrastructure in face-to-face learning.